PKM Tentang Pemanfaatan Media Sosial bagi Peserta Didik Sekolah Menengah Pertama - Fredimento, Aurelius; Pareira, Rosalina Andriyani Ebang; Wanti, Kristina (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Social media is one of the products of human intellect whose influence has permeated nearly all levels of society, including students at SMP Negeri Hamar. While these students benefit from positive aspects such as broader social networks and access to various forms of knowledge, they are also increasingly exposed to adverse effects such as reduced academic concentration, the spread of misinformation, and unrestricted access to pornographic content, which may pose significant risks to their character and moral development. In response to these challenges, the Public Service Team of Cristo Re Polytechnic, in close collaboration with SMP Negeri Hamar, carried out a public service program focused on promoting responsible use of social media among junior high school students. The primary objective was to foster students' understanding of the nature of social media, its potential benefits, and the negative impacts that may affect their personal growth and future. This activity was held on April 18, 2025, at the Stasi Watumerak Chapel and employed the Contextual Teaching and Learning (CTL) approach using audiovisual media. The program aimed to (1) raise students' awareness of the rapid development of social media in today's world; (2) encourage responsible and ethical use of social media; (3) highlight the importance of protecting personal data; (4) promote ethical communication in online interactions; and (5) help students manage their social media usage so it does not interfere with study and rest time. The interactive and engaging implementation of the CTL method encouraged active student participation and critical reflection, leading to the discovery of positive values in social media that can support their personal development. This awareness is expected to guide students toward the wise and responsible use of social media as a tool for building social relationships and developing essential digital competencies for the future.